2013
DOI: 10.5301/ijao.5000172
|View full text |Cite
|
Sign up to set email alerts
|

A Significant Proportion of Patients Treated with Citrate Containing Dialysate Need Additional Anticoagulation

Abstract: A significant proportion of patients treated with citrate-containing dialysate need additional anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Citrate has several advantages over acetate, including local anticoagulant properties that allow a decrease or even removal of anticoagulation for HD, lower peripheral resistance and better blood pressure control during the procedure [6,7,8,9,10]. Another advantage is an increased HD efficiency when citrate dialysate is used [5].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate has several advantages over acetate, including local anticoagulant properties that allow a decrease or even removal of anticoagulation for HD, lower peripheral resistance and better blood pressure control during the procedure [6,7,8,9,10]. Another advantage is an increased HD efficiency when citrate dialysate is used [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have demonstrated that CD is associated with decreased clotting of the HD circuit in comparison with the conventional intermittent saline-flushing treatment [2], increased small and medium solute clearance [3], decreased acidosis [4], and improved anemia [5]. Because CD has gained popularity and its effect on heparin dose is unclear, we aimed to de-DOI: 10.1159/000495025 termine the minimum heparin dose that can be used with CD, considering the possibility of avoiding heparin altogether. The secondary outcomes assessed were the effects of CD on other parameters: acid-base derangement, adequacy of dialysis, and hemoglobin level.…”
mentioning
confidence: 99%
“…Citrate-enriched dialysate, compared to intermittent saline flushes given to patients with a high-risk of bleeding, has also been associated with less thrombus formation in venous air traps [21]. However, another study showed that a significant proportion of patients treated with citrate-dialysate, compared to dialysis with low molecular-weight heparin, needed additional anticoagulation due to clot formation although the URR did not differ between these groups [1]. Moreover, Evenepoel et al [10] showed that citrate, when used as RCA, led to a lower clotting rate necessitating premature termination of the dialysis session compared to the use of heparin-coated AN69ST membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that citrate dialysate is associated with a decreased need for anticoagulation, and hence there is a lesser risk of clotting within the HD circuit [11]. Citrate dialysate is also well tolerated [1,12,13]. It is not associated with the development of severe calcium or acid-base disorders, even when higher citrate loads are used [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation